English Language teaching: Methods and Teaching Aids used by Secondary School Teachers in Mizoram, India (International Journal of Food and Nutritional Sciences, 2022)
In Mizoram, a state located in the north eastern region of India, teaching and learning of English as a second language is often faced with problems of understanding on the part of students which leads to failure and even increase in dropout rates. Teachers are found to be facing certain problems in selecting their methods of teaching in order to deal and teach different kinds students at secondary level of education